Diaphanization techniques for studying the anatomy of human teeth (Research, Society and Development, 2022)
The internal morphology of the root canals differs from the external anatomy of the tooth root, with several variations still little described in the literature. Diaphanization is an effective, simple and fast method for the analysis and preservation of structures or tissues. Because it is easy to use and low cost, it is a practical method for studying the topography of the endodontic. This study is an integrative literature review, whose search was carried out in the SciELO, MEDLINE and LILACS databases. Research articles were included that answered the guiding question: “which methods used to clear human teeth show satisfactory results in the samples for morphological analysis?” 106 results were found, of which 6 met the criteria and were included in this review. During the diaphanization process, chemical solvents were used by the authors, namely: xylol, methyl salicylate, EDTA and citric acid. Diaphanization stands out for providing a three-dimensional analysis of the teeth, preserving their morphology. This analysis, when compared to other techniques, such as radiographs, presented a more detailed visualization. Furthermore, additional studies will be needed to assess whether other solvents, such as organic ones, which do not present toxicity, are viable for the process of clearing teeth, since they must remain stored in the solvent in which they were cleared.